Perbedaan Hasil Belajar Menggunakan Model Problem Based Learning dengan Media Animasi dan Media Gambar - Rizka Aditya Damayanti; Dadang Kurnia; Santa Santa (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2022)
This study aims to determine the differences in learning outcomes using a problem based learning model with animated video media and image media for class V SDN Cicadas 02, Bogor Regency. This type of research is a quasi-experimental. The population consisted of classes V-A and V-D which consisted of 71 people. The research was conducted in three meetings in each class group. Sampling was carried out using a purposive sampling technique. The research data was collected using a pretest and posttest. Data analysis was carried out with the n-gain test, normality test, and homogeneity test as a prerequisite test before testing the hypothesis (t test). The results of data analysis obtained t-count (2.711) > t-table (1.999566) for a significance of 5%. Based on the test criteria, then H0 is rejected and Ha is accepted. Based on the results of this study, it can be concluded that there are differences in the learning outcomes of the Objects in Economic Activities sub-theme using a problem based learning model with animated video media and image media for class V SDN Cicadas 02 Bogor Regency in the 2021/2022 academic year.